In situ monitoring of chlorophyll a fluorescence in Nannochloropsis oceanica cultures to assess photochemical changes and the onset of lipid accumulation during nitrogen deprivation - Carneiro, Mariana (2021)
In situ chlorophyll a fluorescence measurements were applied to monitor changes in the photochemical variables of Nannochloropsis oceanica cultures under nitrogen-deplete and nitrogen-replete (control) conditions. In addition, growth, lipid, fatty acid, and pigment contents were also followed. In the control culture, growth was promoted along with pigment content, electron transport rate (ETR), and polyunsaturated fatty acids, while total lipid content and fatty acid saturation level diminished. Under nitrogen-deplete conditions, the culture showed a higher de-epoxidation state of the xanthophyll cycle pigments. Fast transients revealed a poor processing efficiency for electron transfer beyond Q(A), which was in line with the low ETR due to nitrogen depletion. Lipid content and the de-epoxidation state were the first biochemical variables triggered by the change in nutrient status, which coincided with a 20% drop in the in situ effective quantum yield of PSII (Delta F'/F-m'), and a raise in the V-j measurements. A good correlation was found between the changes in Delta F'/F-m' and lipid content (r = -0.96, p < 0.01). The results confirm the reliability and applicability of in situ fluorescence measurements to monitor lipid induction in N. oceanica.